Avaliação da eficácia e segurança da farmacoterapia da leishmaniose visceral - Melo, Edson Carvalho de [UNESP] (2013)
American Visceral Leishmaniasis (AVL) is a disease that causes significant mortality. Since the past two decades it is disseminating widely in Brazil. Its etiologic agent is Leishmania infantum chagasi, a vector-borne parasite. Traditionally, AVL was regarded as an endemic disease in Northern and Northeastern States, but it has emerged in urban areas and in Southeastern States. In São Paulo State, autochtonous cases occur since 1999. Therapeutic options for AVL are scarce, and all leishmanicidal drugs are associated with failures, relapses and serious adverse events. Meglumine antominiate has been the first-line therapy in Brazil for many decades. Lately, amphotericin B deoxycholate or in liposomal formulation have been recommended for more severe cases. However, those data are extrapolated from studies conducted in India, Africa and Europe. The study was designed to fulfill this gap. It was a multicenter, randomized, open-label study that compare the efficacy and safety of three therapeutic options: meglumine antimoniate, amphotericin B deoxycholate and liposomal amphotericin B. Patients with parasitological confirmation of AVL were included. Those that were coinfected with HIV or who had immune-supressing conditions or pregnancy were excluded. We also excluded those for whom governmental guidelines recommended the use of amphotericin B. Patients were followed with physical examination and laboratory tests on days 0, 3 , 14, 30, 90 and 180. We included 59 subjects, 33 of whom completed follow-up (11 in each arm). Clinical response was similar for all groups. However, those receiving amphotericin were more likely to have early recovery of hemoglobin dosage and white cell counts, as well as serum albumin. There was a discrete tendency of better response with liposomal amphotericin. Nephrotoxicity was striking among those receiving amphotericin deoxycholate (42%), an incidence significantly higher than that observed with the other ...